Acetyl-L-carnitine for patients with hepatic encephalopathy (2014)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the clinical benefits and harms of acetyl-L-carnitine for treating patients with hepatic encephalopathy